1966
DOI: 10.1104/pp.41.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Density Gradient Distribution of Mitochondrial Protein and Enzymes from Preclimacteric and Climacteric Pears

Abstract: Suimnary. Mlitochondrial fractions isolated fronm pears (Pyrus coknimmnis L.) at the climacteric minimum alnd peak were sulbjected to sucrose densitv gradient centrifugation. The distribution of protein and specific activities of 3 enzvmles from this mitochondrial fraction were investigated.Cytochrome oxidase specific activity remained associated with the particulate fraction and increased slightly during the period in which respiration of the whole fruit reached its climacteric peak. Catalase and acid phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The activities of several mitochondrial enzymes were also assessed in mitochondrial isolates from banana 20 , lemon 21 , and mango 22 . The introduction of density gradient centrifugation using sucrose 23 or Percoll 24 greatly enhanced the purity of mitochondria isolated from fruits, making it possible to characterize the mitochondrial proteomes of various fruit crops. Subsequently, proteomic analysis revealed that oxidative damage and carbonylation modification of mitochondrial proteins are widely involved in the regulation of fruit ripening and senescence [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…The activities of several mitochondrial enzymes were also assessed in mitochondrial isolates from banana 20 , lemon 21 , and mango 22 . The introduction of density gradient centrifugation using sucrose 23 or Percoll 24 greatly enhanced the purity of mitochondria isolated from fruits, making it possible to characterize the mitochondrial proteomes of various fruit crops. Subsequently, proteomic analysis revealed that oxidative damage and carbonylation modification of mitochondrial proteins are widely involved in the regulation of fruit ripening and senescence [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…Micros copically they are present in tobacco stem and ca llus tissue (49), in oat coleoptile (49,159,176), and in etiolated leaf tissue (P. J. Gruber & E. Newcomb, personal communication). The detection of ca talase activity on sucrose gradients of particles suggests that microbodies are present in mung bean hypocotyl (129), oat coleoptiles (176), and ripening pears (107 ). Microbodies are present in th e developing Sym plocarpus spadix (10; Ph .…”
Section: Introductionmentioning
confidence: 98%